Altered Rhythmicity, Depressive Ruminative Thinking and Suicidal Ideation as Possible Correlates of an Unrecognized Autism Spectrum in Patients with Borderline Personality Disorder - Ivan Mirko Cremone; Liliana Dell’Osso; Benedetta Nardi; Federico Giovannoni; Francesca Parri; Cristiana Pronestì; Chiara Bonelli; Gabriele Massimetti; Stefano Pini; Barbara Carpita (Brain Sciences, 2024)
Background/Objectives: Recent research has explored the presence of subthreshold autistic traits (ATs) in individuals with borderline personality disorder (BPD), suggesting that these traits may contribute to the severity of BPD symptoms and increase the risk of other mental health issues, including suicidal behaviors. This study aims to investigate the relationship between ATs and affective symptoms, such as mood instability and suicidality, in people diagnosed with BPD. Methods: A total of 48 subjects with BPD were assessed with self-report questionnaires including the Adult Autism Subthreshold Spectrum (AdAS Spectrum), the mood spectrum self-report version (MOODS-SR) and the ruminative response scale (RRS). Results: Subjects with significant ATs scored higher than BPD subjects in all domains and in the total score of AdAS Spectrum, RRS, and MOODS-SR, as well as in the items investigating suicidality. RRS total score, its depression domain, and the MOODS-SR rhythmicity domain, as well as suicidality, were predictors of the presence of ATs. Conclusions: Our data confirm the relationship between the presence of clinically significant ATs and affective symptoms, ruminative thinking, and suicidality in patients with BPD.